Perceived Cultural Distance in Healthcare in Immigrant Intercultural Medical Encounters. (10th December 2019) - Alizadeh, Somayeh; Chavan, Meena
Abstract: This article responds to the paucity of empirical research on the impact of patient‐provider ethno‐cultural distance and providers' cultural competence on the quality of healthcare service in migrant intercultural medical encounters in Australia. A cross‐sectional study was conducted with 447 patients, consisting of 195 Caucasian and 252 non‐Caucasian patients from six outpatient clinics in New South Wales, Australia. Structural equation modelling was used for data analysis. The findings demonstrated that cultural distance is an influential factor in perceived quality of outpatient care. Caucasian and non‐Caucasian patients' perception of cultural distance between their physicians and themselves affected their service quality ratings of their physicians' professionalism, empathy and expertise. This is the first study on healthcare service quality in outpatient clinics in Australia for Caucasian and non‐Caucasian patients. Policy implications suggest intervention strategies and the need for cultural competence education in medical and health curricula in medical schools and clinical practices.